Your year in art : a project for every week of the year to overcome blank-page anxiety and inspire creative exploration - Ward, Chelsea (Walter Foster, 2018)
"Leave your artistic anxiety behind with 52 weeks of hearty inspiration. Your Year in Art is a must-have guide to rouse your creative side. Designed for aspiring, beginning, and practicing artists looking to hone their skills, Your Year in Art is packed with unique projects and encouraging instruction. The mission of Your Year in Art is to sharpen your art skills and quiet your inner critic by showing you how to draw habitually and spontaneously. As you build your craft, techniques, and confidence, this guide encourages you to create in a way that celebrates your individuality. Fifty-two clever drawing prompts, along with tips and tricks, from expert illustrator Chelsea Ward will get your creative juices flowing. Weekly challenges include making a "self-portrait" by sketching things that describe you; practicing mark-making techniques like cross-hatching and stippling; filling a sketchbook page with drawings on a theme, like potted plants or fire hydrants; and adding water to ink drawings to practice wash techniques."--